Frequência da Talassemia Alfa – Deleções 3.7kb e 4.2kb em indivíduos da Região Metropolitana de Manaus - Amazonas - Anselmo, Fernanda Cozendey (2019)
Alpha thalassemia, one of the most common monogenic diseases in the world, is a heterogeneous group of hereditary changes caused by those who affect the alpha (α) regulatory genes and promote imbalance in the market in hemoglobin levels due to the loss of one or more α genes. The 3.7Kb deletion is the most frequent worldwide and, in Brazil, varied 20 and 35%, while it is mainly concentrated, being more predominant in Afro-descendants. A major cross-sectional study was carried out with the aim of characterizing an alpha thalassemia, comprising -α3.7 and -α4.2 deletions, estimating its frequency in a case of the Metropolitan Region of Manaus-Amazonas. The deletion was investigated by GAP-PCR for -α3.7 and Multiplex-PCR for -α4.2. The sample size included 2798 municipalities of the region, comprising the cities of Iranduba (N = 232), Itacoatiara (N = 301), Manacapuru (N = 287), Presidente Figueiredo (N = 370), Coari (N = 263) and the capital, Manaus (N = 1345). The samples were collected from hospitals and/or health centers in each city. Specifically, in Manaus, the samples were stratified between care at health centers (N = 356) and a specific group of blood donors seen at FHEMOAM (N = 989). All samples were submitted to the hemogram and by the dosage of Ferritin and Serum Iron (Bioclin® KIT). DNA extraction was performed using Biopur Mini Spin Plus kit, stored at -20°C and further processed. Alpha thalassemia was found in 7.9% of the general population (6.0% heterozygous and 1.9% homozygous), as the variables analyzed among the patients were statistically significant (<0.001) among hematological parameters, except between Serum iron and Ferritin dosages. In this group, 158 microcytic and hypochromic subjects were found, with a frequency of 40.68%. The prevalence of -α3.7 was 5.35% in blood donors. The number of leukocytes and platelet counts did not differ significantly. As might be expected, hematological data were more reduced, considering an average among normal individuals (p <.001). This is a study that presents values of hematological parameters, especially MCV and HCM are lower in donors with iron deficiency, while when associated with α-thalassemia and may be useful in discriminating different types of microcytic anemia. In conclusion, we believe that screening for the thalassemia trait should be built on genetic and at the same time prenatal databases, as well as the existence of a standard blood test prior to donating blood. It should be noted the first study to perform a screening of alpha deletions in the general population and blood donors of the Manaus region